Woodrow Wilson USA - Morton, Brian 1954- (Haus histories, 2008)
A study of the life of Woodrow Wilson, from his early years during the American Civil War, through his academic and political career and America & rsquo;s involvement in the First World War, to Wilson & rsquo;s role at Versailles, including the construction of his Fourteen Points and his principles for the reformation of Europe.